Upaya Meningkatkan Kreativitas Anak Melalui Metode Menggambar di Desa Karangasem Kabupaten Lamongan - Yulias Wulani Fajar; Lailatul Izzah (Universitas Trunojoyo Madura, 2014)
Creativity allows humans improving their quality of life. Nothing could be more well-being of the community and our country depends on the creative contribution, in the form of new ideas, new inventions and new technologies of members of the community. Everyone has a different creativity and education can be developed on the right. This study aims to determine the level of children’s creativity through drawing method. Study conducted by collecting data through observation, interviews and documentation. Research results conclude that there are many potential Karangasem village in children that can be explored and one of them increases children’s creativity through drawing method. From these results it can be suggested that the local people, especially in the elderly is more disciplined in supervising children when learning, and doing things that can increase the child’s creative thinking as the method of drawing that will hone fine motor.